Dialysis Dependence Is Associated With Significantly Increased Odds of Perioperative Adverse Events After Geriatric Hip Fracture Surgery Even After Controlling for Demographic Factors and Comorbidities. (August 2019) - Ottesen, Taylor D.; Yurter, Alp; Shultz, Blake N.; Galivanche, Anoop R.; Zogg, Cheryl K.; Bovonratwet, Patawut; Rubin, Lee E.; Grauer, Jonathan N.
Abstract : Introduction: Previous studies evaluating the risk of perioperative adverse events after hip fracture surgery for dialysis-dependent patients are either institutional cohort studies or limited by patient numbers. The current study uses the National Surgical Quality Improvement Program database's large national patient population and 30-day follow-up window to address these weaknesses. Methods: National Surgical Quality Improvement Program databases (2006 to 2016) were queried for patients aged 60 years or older who underwent hip fracture surgery. Differences in 30-day outcomes based on preoperative dialysis dependence were compared using risk-adjusted logistic regression and coarsened exact matching for adverse events, need for revision surgery, readmission, and mortality. The proportion of adverse events that occurred before versus after discharge was also assessed. Results: A total of 288 dialysis-dependent and 16, 392 non–dialysis-dependent patients met the inclusion criteria. Matched populations controlling for demographic factors (ie, age, sex, body mass index, and functional status) and overall health (American Society of Anesthesiologists class) found dialysis-dependent patients to be associated with significantly greater odds of any adverse event (odds ratio [OR] = 1.90), major adverse event (OR = 1.77), and unplanned readmission (OR = 2.48). Increased odds of minor adverse event (OR = 1.05), return to the operating room (OR = 1.66), and death (OR = 1.42) within 30 postoperative days were also found but were not statistically significant. Discussion: Even after controlling for demographics and health status, geriatric dialysis patients undergoing surgery for hip fracture are at significantly greater odds of adverse outcomes. Because of increased risks for geriatric dialysis patients undergoing surgery for hip fracture, surgical caution, patient counseling, and heightened surveillance must be observed throughout the perioperative period for this fragile population. Furthermore, hospitals and physicians must take the increased risks associated with dialysis into account when considering bundled payment reimbursement strategies and resource allocation for hip fracture care.